Salivary Stress-Related Responses in Tinnitus: A Preliminary Study in Young Male Subjects with Tinnitus - Alsalman, Ola A.; Tucker, Denise; Vanneste, Sven (Frontiers in Neuroscience, 2016)
Objective: This preliminary study examined if baseline measures of stress-related biomarkers as measured by salivary secretions of specific autonomic (measured by salivary α-amylase), endocrine (measured by salivary cortisol), and immune (measured by salivary neopterin) responses are greater in male subjects with tinnitus in response to an induced-stress task. Method: Twenty male subjects with no significant hearing loss, 10 with tinnitus and 10 without tinnitus were enrolled in this study. Salivary secretions were collected before and after the induced stress task at four different time intervals. Results: Salivary α-amylase levels were lower in the tinnitus group in comparison to subjects without tinnitus, suggesting impaired sympathetic activity in the subjects with tinnitus although these levels remained stable throughout the stress experiment. While no significant effects could be obtained for salivary cortisol or neopterin, salivary neopterin levels were trending toward significance over all measurements. Behavioral measures of stress were found to correlate negatively with measures of salivary α-amylase and salivary neopterin. Conclusion: The results of this study suggest impaired stress-related salivary α-amylase mechanisms in male subjects with tinnitus, as evidenced by the different stress reactions induced in the endocrine system (as measured by salivary cortisol) and the immune system (as measured by salivary neopterin).